Kekuatan mekanik komposit diperkuat serat alam selulosa - N. H. Sari (Universitas Mataram, 2018)
This study aims to analyze the tensile and impact strengths of three different types of composites. Composites are made from polyester resins with different fibers; Pandannus Amariliofius fiber, Eichhornia Crassipes fiber and Coconut Fronds fiber. The three composite types have a polyester and fiber composition ratio namely 50:50, 60:40, 70:30, 80:20, and 90:10 (% volume). Manufacture of composite samples using a hot press technique. The results indicate that the tensile strength and Izod impact strength from the coconut fronds fiber reinforced composite is better than the other composites studied, due to the incorporation of fibers in the polyester resin matrix. These results suggest that in terms of their mechanical properties, the performance of the composite properties reinforced by the cellulosic natural fibers can be a candidate to replace artificial wood products.